KEEFEKTIFAN KALIMAT DALAM ARTIKEL ILMIAH MAHASISWA: ANALISIS SINTAKSIS DAN IMPLIKASINYA TERHADAP KETERAMPILAN MENULIS AKADEMIK - Rostikawati, Yeni; Desi Ratna Ayu; Dede Dudu Abdul Rahman; Andoyo Sastromiharjo (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2026)
This study aims to analyze sentence effectiveness in students’ scientific articles based on syntactic aspects and to examine its implications for academic writing skills. The research is motivated by the frequent occurrence of ineffective sentences in students’ academic writing, such as syntactic function, lack of parallelism in complex sentences, redundancy, and improper use of punctuation and conjunctions. The study employed a descriptive qualitative approach with linguistic content analysis. Data were collected from twelve student scientific articles from the Digital Business Study Program selected through purposive sampling. The data were analyzed using the Miles, Huberman, and Saldaña (2014) procedure, which includes reduction, display, and conclusion drawing. The findings reveal that the most dominant errors lie in the improper use of conjunctions and the omission of essential syntactic elements. These errors affect the clarity and coherence of scientific arguments. The implications highlight the need for strengthening students’ academic writing through applied syntax instruction focusing on contextual and rhetorical sentence analysis.